New perspectives in the 21st century Central American cinema - García Diego, Charo (2022)
This article is proposed as a valuable contribution to bring Central American cinema closer to all the people who inhabit the region and to foreigners who feel a particular interest in the cinema made in Guatemala, Nicaragua, El Salvador, Honduras, Costa Rica and Panama. Is Central American cinema made in the 21st century a space for a socio-political reflection? Does the treatment of its themes lead directors to claim causes? How do Central American film directors approach ethics and aesthetics in their artistic productions? Central American cinema research is based on the answer to these questions. An important charge of denunciation accompanies films that contemplate migration in its two aspects, forced and voluntary in search of a better quality of life. The maras are thebackbone of violence together with the re-enactment of civil wars and the disappeared. Collective memory, persecution of indigenous peoples, sexual diversity, the power of religion in its evangelical version, and motherhood as the only response to unwanted pregnancies constitute some of these new perspectives.